EFEKTIVITAS PERATURAN DAERAH PROVINSI BALI NOMOR 1 TAHUN 2017 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DALAM MENCEGAH PENCEMARAN AIR TANAH - PRATHAMA, ANAK AGUNG GEDE AGUNG INDRA; Yogiswara, I Gede Mahatma; Hutama, I Dewa Made Adhi (Jurnal Yustitia, 2024)
Bali is a tourist destination that is favored by many domestic and foreign tourists. However, the high consumption activity of local people and tourists in the province produces quite a lot of waste generation. Based on data from the Ministry of Environment and Forestry (KLHK), the city of Denpasar produces 915.5 thousand tons of waste generation throughout 2021. This makes Bali the 8th largest waste-producing province in Indonesia. legal research that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. Conclusion of the Effectiveness of Bali Province Regional Regulation Number 1 of 2017 Concerning Environmental Protection and Management in Preventing Groundwater Pollution in the Legal Area of ​​the Denpasar City Environment Service has not been effectively implemented, because based on data on public complaints and data on prosecution of violations there is still an increase from year to year, starting from 2019 to 2022, so it is proven that the enforcement that has been carried out so far has not provided a deterrent effect, because the authorized apparatus related to this Regional Regulation, especially the Civil Service Police Unit, has not been maximal in carrying out enforcement of Constraints and Efforts from the Denpasar City Environment Service in Preventing Groundwater Pollution in the City of Denpasar, namely the obstacle is the participation and supporting capacity of the community in protecting the environment, especially in the application of this Regional Regulation which has not been maximized, and because of the lack of facilities and infrastructure owned in carrying out investigations to detect sources of pollution